2014
DOI: 10.1108/pr-02-2012-0019
|View full text |Cite
|
Sign up to set email alerts
|

Linking justice, trust and innovative work behaviour to work engagement

Abstract: Purpose – The purpose of this paper is to examine the effects of contextual variables – organisational justice (procedural justice, interactional justice and psychological contract) and trust – on work engagement. Design/methodology/approach – The paper reports a quantitative study of 323 managers working in manufacturing and pharmaceutical organisations based in western India. Drawing from social exchange theory, this paper tests the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
305
1
15

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(343 citation statements)
references
References 145 publications
(149 reference statements)
22
305
1
15
Order By: Relevance
“…The indices of adjustment were adequate and the residuals are acceptable. This solution is corroborated by some international studies and may have been found because engagement, as measured by UWES, is a construct with high correlation between items (Agarwal, 2014;Chutghtai & Buckley, 2013;Federici & Skaalvik, 2011;Hakanenet al, 2008;Mauno et al, 2007;Weigl et al, 2010). In Brazil, the psychometric analysis of the scale confirms a one-factor solution as more parsimonious both for the UWES-17 as for the UWES-9.…”
Section: Final Considerationssupporting
confidence: 60%
“…The indices of adjustment were adequate and the residuals are acceptable. This solution is corroborated by some international studies and may have been found because engagement, as measured by UWES, is a construct with high correlation between items (Agarwal, 2014;Chutghtai & Buckley, 2013;Federici & Skaalvik, 2011;Hakanenet al, 2008;Mauno et al, 2007;Weigl et al, 2010). In Brazil, the psychometric analysis of the scale confirms a one-factor solution as more parsimonious both for the UWES-17 as for the UWES-9.…”
Section: Final Considerationssupporting
confidence: 60%
“…Most studies of the relationship between LMX and IWB have confirmed that the former has a positive effect on the latter (Altunoglu & Gurel, 2015;Kheng et al, 2013) and that LMX is an important antecedent of IWB (Xerri, M., 2013, Agarwal, 2014. A high level of LMX quality between employees and supervisors will encourage ijbm.ccsenet.org International Journal of Business and Management Vol.…”
Section: Relationship Between Lmx and Iwbmentioning
confidence: 99%
“…Also, IWB is broader than proactive work behavior (Crant, 2000;Parker, Williams & Turner, 2006), which concentrates on implementing change, but does not specifically cover the initiation element of the innovating process. Although IWB does benefit the organizations, it is performed in a discretionary manner and may not be rewarded in a direct or formal sense (Agarwal, 2014). Such behavior encourages innovation once it is recognized as a norm within the organization (Martins & Martins, 2002).…”
Section: Innovative Work Behaviormentioning
confidence: 99%
“…The extant literature advances a link between employee engagement and organizational justice (Li 2012), with perceived organizational justice found to be an important element in employee engagement (He et al 2014). Equity theory and SET provide theoretical explanations for employee engagement in discretionary activities (as contended by Agarwal 2014, Biswas et al 2013, Ghosh et al 2014, He et al 2014, Li 2012, Saks 2006.…”
Section: Employee Engagementmentioning
confidence: 99%